1998
DOI: 10.1128/jvi.72.8.6437-6441.1998
|View full text |Cite
|
Sign up to set email alerts
|

Transfectant Influenza A Viruses with Long Deletions in the NS1 Protein Grow Efficiently in Vero Cells

Abstract: We established a reverse genetics system for the nonstructural (NS) gene segment of influenza A virus. This system is based on the use of the temperature-sensitive (ts) reassortant virus 25A-1. The 25A-1 virus contains the NS gene from influenza A/Leningrad/134/57 virus and the remaining gene segments from A/Puerto Rico (PR)/8/34 virus. This particular gene constellation was found to be responsible for the ts phenotype. For reverse genetics of the NS gene, a plasmid-derived NS gene from influenza A/PR/8/34 vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(84 citation statements)
references
References 30 publications
(31 reference statements)
4
75
0
5
Order By: Relevance
“…Effects of NS1 mutations on pH1N1 virus growth and induction of IFN-␤ in cell cultures. IAV NS1 has previously been shown to play a significant role in viral pathogenesis in vivo (15,44,45). Generally, mutations decreasing the ability of NS1 to counteract host innate immune responses have been shown to reduce the virulence of IAV in vivo (46,47).…”
Section: Resultsmentioning
confidence: 99%
“…Effects of NS1 mutations on pH1N1 virus growth and induction of IFN-␤ in cell cultures. IAV NS1 has previously been shown to play a significant role in viral pathogenesis in vivo (15,44,45). Generally, mutations decreasing the ability of NS1 to counteract host innate immune responses have been shown to reduce the virulence of IAV in vivo (46,47).…”
Section: Resultsmentioning
confidence: 99%
“…NS1 is a nonstructural protein encoded by segment 8 of influenza virus A. Genetic analyses of NS1 have shown that viral replication, spread, and pathogenesis are very dependent on the function of this protein (3,4,6,10,11,13,17,18,22,27,29,30,36,63,66,74). This satisfies an important criterion for an anti-influenza virus target, since drugs that inhibit the action of the target must be able to slow virus production and/or pathogenesis as a consequence.…”
mentioning
confidence: 99%
“…The EHF sequels develop in the presence of a cytokine storm and immunoparalisis due to infection of macrophages and dendrite cells and a block of synthesis and functional activity of interfer ons [23][24][25][26]. The Ebola virus came into focus of relevant studies [22,23] soon after a discovery of virus proteins acting as interferon antagonists [29]. As a result, VP35 was identified as a protein that to blocks interferon pro duction in early infection [22,23].…”
Section: Clinical Presentation Of Ebolamentioning
confidence: 99%
“…Large scale generation of immune complexes in circulation is also considered to be a factor that provokes blood clotting [28,[43][44][45]. The disease outcome is usually determined on days 6-11, when either the acute phase crisis resolves or a transition to the terminal stage occurs [14,29,[31][32][33][34][35][36][37][38][39]. This circumstance shows that the therapy window is limited and that a medical decision is to be made within a short while; it is therefore of immense impor tance to detect the turning period [25,[40][41][42]46].…”
Section: Clinical Presentation Of Ebolamentioning
confidence: 99%